Are Young Women More Potential to Commit Suicide? - Patricia Wulandari; Rachmat Hidayat (HM Publisher, 2020)
Introduction: Convenience in various aspects of life in fact does not guarantee people live happier. Every year around the world around one million people die from suicide. One of the most consistent findings in suicide research is that women make more suicide attempts (tentament suicide) than men. This research is the first research conducted as an effort to increase the awareness of all medical potentials of young women to commit suicide. Methods: This research was qualitative research with an in-depth interview approach to respondents. The subjects of this study were patients with a diagnosis of tentamen suicide who consulted the Cattleya Consultation Center, Palembang, Indonesia. Results: All subjects with a tendency to commit suicide were female (100%) with a young age, ie the youngest age was 16 years and the oldest was 28 years. Women at this age are classified as young and productive age. It was found that most of the patients had avoidant personality traits (43%). In addition, the factors that triggered the emergence of tentamen suicide in some respondents were social and environmental factors (44%), namely in the form of friendship factors (peer groups), and the experience of bullying. Conclusion: Young women have the potential to do tentamen suicide.